PENGARUH PENGGUNAAN APLIKASI DIGITAL TERHADAP EFEKTIVITAS KERJA PEGAWAI - Choirinisa, Aulia Asri; Ikhwan, Khairul (Transpublika Publisher, 2022)
In this 4.0 era, many companies have switched to using digitization for work purposes, implementing digital applications that aim to make it easier for the people involved in their work processes. This literature-based research can provide benefits in the form of knowledge relevant to the research conducted, namely looking for information on the relationship between the use of digital applications and work effectiveness, where the data used is obtained from relevant research and previous studies related to the topic. The results of relevant research and previous research are useful for strengthening theories, ideas and phenomena that are related and have an effect on research variables. In this study, the results of a review of the use of digital applications with various types and their impact on employee work results will determine the level of work effectiveness.